Personality-Environment Congruency of Land Settlement Youth Entrepreneurs in Malaysia - Yunus, Ahmad Rozelan; Aris, Amir; Abdul Majid, Izaidin; Md Saad, Mohd Shamsuri (2013)
The purpose of this study was to investigate the mediating effect of person-environment congruency on the relationship between organisational culture and organisational commitment. Data were obtained from entrepreneur youth who were member and in the leadership position of FELDA Youth Organisation in Malaysia (n=408). Person-environment congruency was found to be a significant mediator of the relationship between organisational culture and organisational commitment. This has wide-ranging implications for organisational development consultants who intend to shape the culture of various organisations, on the assumption that certain organisational cultures directly lead to certain desirable employee outcomes. Leaders need to pay attention to not only their organisational culture such as training, rewards, teamwork and communication, but to also ensure that they are aimed towards improving the fit between individuals and their work environment. Whereas previous research tends to look at P-E congruency as a predictor of employee outcomes, this is one study to provide evidence of P-E fit as a mediator of the relationship between organisational culture and organisational commitment.